1991
DOI: 10.1037/0022-0167.38.2.167
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of coping styles and gender differences with farmers in career transition.

Abstract: This study examined the role of career-related variables (vocational identity, career barriers) and coping variables (problem-solving appraisal and coping style) in predicting (a) depressive symptomatology and (b) perceived stress, control, and progress in the career transition of a farm population in crisis. The sample for this study consisted of 44 male and 35 female farmers with respective mean ages of 39.2 and 41.6 years. Results indicated that significant differences exist in the way farm men and women re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 39 publications
(50 reference statements)
1
27
0
1
Order By: Relevance
“…A study of farm families in career transitions (Heppner, Cook, Strozier, & Heppner, 1991) indicated that problem-directed coping was related to increased progress and increased perception of control for women but not for men. In a study of men and women coping with organizational downsizing (Armstrong-Stassen, 1998), active coping was associated with a lower perceived threat ofjob loss among women but not men.…”
Section: Resultsmentioning
confidence: 98%
“…A study of farm families in career transitions (Heppner, Cook, Strozier, & Heppner, 1991) indicated that problem-directed coping was related to increased progress and increased perception of control for women but not for men. In a study of men and women coping with organizational downsizing (Armstrong-Stassen, 1998), active coping was associated with a lower perceived threat ofjob loss among women but not men.…”
Section: Resultsmentioning
confidence: 98%
“…A number of researchers (e.g., Heppner, Cook, Strozier, & Heppner, 1991;Lucas & Epperson, 1990) have utilized the Barriers Scale of My Vocational Situation (Holland, Daiger, & Power, 1980) to assess perceived barriers. The Barriers Scale consists of four yes/no items that address personal obstacles to feeling confident in one's abilities, barriers to obtaining information, and perceived external barriers to accomplishing an occupational goal (Walsh & Betz, 1995) and has yielded low KR20 reliability estimates (r = .45; Holland et al, 1980), and test-retest reliability coefficients (r = .36 for a 3-to 5-month time period; Lucas, Gysbers, Buescher, & Heppner, 1988).…”
Section: Assessing Perceived Barriersmentioning
confidence: 99%
“…Ayrıca problem çözme becerilerini yüksek olarak algılayan bireylerin yüksek özgüven duygusuna sahip oldukları, karşılaştıkları olaylar karşısında fazla kaygılanmadıkları ve problemin çözümüne yönelik daha dikkatli davrandıkları görülmüştür (Heppner, Stephen, Stroizer & Heppner, 1991;Rosenberg, 1989). Ancak günümüz dünyasında matematiksel problemlerin çözümünün sadece bireylerin kendilerine güvenmeleriyle ilgili olmadığı aynı zamanda probleme yönelik matematiksel dilin iyi anlaşılmasıyla da ilişkili olduğu bilinmektedir (Akkaya & Memnun, 2012).…”
Section: Introductionunclassified